2022
DOI: 10.18502/ijph.v51i8.10257
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Knowledge in Children on Self-Protection of Sex-ual Abuse: A Systematic Review

Abstract: Background: Sexual child abuse is a form of anti-social behavior with the children that cause potential harm to the health, development and dignity of the child. Knowledge of children about these issues can help to protect themselves against sexual abuse. This study aimed to review systematically available documents about the importance of knowledge on self-protection of sexual abuse in children. Methods: In this systematic review, “sexual abuse”, “self-protection” and “knowledge” were searched in Scopus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…These findings are in agreement with the previous studies which indicated that teaching the children to identify possible situations of abuse and learning to use of self-protection skills against sexual harassment can help to raise their awareness and subsequently minimize these antisocial behaviors in a society. (26) (17) (10) (27) Furthermore, the current study multivariate analysis confirmed that the implementation of the program proved to be an independent positive predictor of the preschool children's awareness scores, which indicated the success of the program. This is certainly attributed to the appropriate design of the content and process of the program which was developed on a picture-based format to be applicable to and built upon the age and social circumstances that preschoolers would encounter in the real world, enhancing active participation and interactions of the children.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…These findings are in agreement with the previous studies which indicated that teaching the children to identify possible situations of abuse and learning to use of self-protection skills against sexual harassment can help to raise their awareness and subsequently minimize these antisocial behaviors in a society. (26) (17) (10) (27) Furthermore, the current study multivariate analysis confirmed that the implementation of the program proved to be an independent positive predictor of the preschool children's awareness scores, which indicated the success of the program. This is certainly attributed to the appropriate design of the content and process of the program which was developed on a picture-based format to be applicable to and built upon the age and social circumstances that preschoolers would encounter in the real world, enhancing active participation and interactions of the children.…”
Section: Discussionsupporting
confidence: 62%
“…Likewise, Yu et al (23) , who emphasized that child's age is a significant factor in determining their knowledge of sexual issues and that older children have appropriate awareness and training on selfprotection strategies. As well, Rahimi Khalifeh Kandi et al (27) found that children between the ages of 9 and 11 had greater knowledge than children between the ages of 6 and 8, except when the child had learned the essential information from their parents. However, Tirtawinata (4) concluded that children can protect themselves from adult sexual harassment when they have proper knowledge and attitude towards sex organs in young age as early as three.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Despite being the closest adults to children aside from parents, teachers are crucial professionals for providing students with CSA information (Jin et al, 2017 ). Children’s knowledge of CSA can be enhanced by receiving comprehensive education from teachers through educational programs (Kandi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%